OCENA ZASTOSOWANIA TECHNOLOGII INFORMACYJNO-KOMUNIKACYJNYCH W PODRĘCZNIKACH DO NAUKI JĘZYKA ANGIELSKIEGO - Piotr J. Malinowski (Neofilolog, 2019)
The aim of the article is to present an analysis of the assessment of the use of information and communication technology (ICT) in conventional textbooks for teaching English. After presenting the theoretical framework of the new core curriculum in terms of autonomy and ICT application, the study describes the way in which ICT tools are integrated or ignored in current English textbooks. The study covered textbooks used in the seventh grade of primary school. Six of the eight (one per publisher) textbooks available on the market were selected for this purpose. Qualitative research comprised a thorough evaluation of tasks which comprised explicit references to ICT. The quality of the analysed didactic materials was determined by the potential level of supporting students’ autonomy by using the coursebook tasks in question, measured through a specially designed Likert scale. The conclusions served to propose changes and improvements to these textbooks.